Antibacterial Activity of Helichrysum italicum Oil on Vegetables and Its Mechanism of Action. Issue 6 (25th May 2015) - Cui, Haiying; Zhao, Chengting; Lin, Lin
Abstract: In the present paper, the chemical composition of H elichrysum italicum oil was analyzed by gas chromatography–mass spectrometry (GC‐MS). Neryl acetate (32.65%) was the main component. The minimum inhibitory concentration and minimum bactericidal concentration of H . italicum oil against several bacteria were evaluated. The results showed that H . italicum oil exhibited high antibacterial activity against all of the bacteria tested. In addition, H . italicum oil also displayed a significant effect on inhibiting the growth rate of surviving E scherichia coli and S taphylococcus aureus in vitro and on vegetables. Meanwhile, addition of H . italicum oil to vegetable exerted a bacteriostatic effect. Besides, the mechanisms of the antimicrobial action of H . italicum oil to E . coli and S . aureus were concluded as that H . italicum oil could disrupt the cell membrane integrity, leading to the losses of intracellular constituents, such as the 260 nm absorbing materials, DNA and ATP. Practical Applications: As a kind of natural, safe spice, H elichrysum italicum oil has been proven to be a good antibacterial agent against a wide range of bacteria at a low concentration and short incubation time. Especially, H . italicum oil exhibits a significant bacteriostatic effect in vegetables. Based on the results, we believe that H . italicum oil can be applied in vegetable processing and preservation.